Construction of Recombinant Lactococcus lactis Strain Expressing VP1 Fusion Protein of Duck Hepatitis A Virus Type 1 and Evaluation of Its Immune Effect - Xiaoting Zhang; Ruihua Zhang; Jingyu Wang; Nana Sui; Guige Xu; Hui Yan; Yanli Zhu; Zhijing Xie; Shijin Jiang (Vaccines, 2021)
With the continuous development of duck farming and the increasing breeding density, the incidence of duck hepatitis A virus type 1 (DHAV-1) has been on the rise, seriously endangering the development of duck farming. To reduce the use of antibiotics in duck breeding, susceptibility risks and mortality, and avoid virulence recovery and immune failure risk, this study aims to develop a new type of mucosal immune probiotics and make full use of molecular biology techniques, on the level of genetic engineering, to modify Lactococcus lactis (L. lactis). In this study, a secretory recombinant L. lactis named MG1363-VP1 with an enhanced Green Fluorescent Protein (eGFP) and translation enhancer T7g10L was constructed, which could express the VP1-eGFP fusion protein of DHAV-1. The animal experiment in ducklings was performed to detect the immune response and protection effect of oral microecologics by recombinant L. lactis. The results showed that oral L. lactis MG1363-VP1 significantly induced the body’s humoral immune system and mucosal immune system to produce specific anti-VP1 IgG antibodies and mucosal secretory immunoglobulin A (sIgA) for DHAV-1 in ducklings, and cytokines including interleukin-2 (IL-2), interleukin-4 (IL-4), interleukin-10 (IL-10), and interferon gamma (IFN-γ). The mortality rate was monitored simultaneously by the natural infestation in the process of production and breeding; notably, the ducklings vaccinated with L. lactis MG1363-VP1 were effectively protected against the nature infection of DHAV-1. The recombinant L. lactis MG1363-VP1 constructed in this study provides a new means of preventing and controlling DHAV-1 infection in the future.